Answer:
-6/5
Step-by-step explanation:
3/2x - 5/4y = 15
-5/4y = -3/2x + 15
multiply each side by (-4/5)
(-4/5)(-5/4y) = (-4/5)(-3/2x + 15)
y = -6/5x - 12
rate of change: -6/5
Answer: B. 2 = 3x + 10x2
Step-by-step explanation:
This is the concept of quadratic equations; We required to find the type of equation that can be solved using the model that has been used to solve the equation such that the answer is:
[-3+-sqrt(3^2+4(10)(2))]/(2(10))
The formual that was applied here was a quadratic formula given by:
x=[-b+\-sqrt(b^2-4ac)]/2a
whereby from the our substituted values above,
a=10,b=3 and c=-2
such that the quadratic equation will be:
10x^2+3x-2
Answer:
Part b would be 4 and c would be 5 and d would be 19
Step-by-step explanation:
So yea do those
Answer:
dam this been up for a long time
Step-by-step explanation:
its just too hard sorry man
I got 65/153 since you actually multiply by the reciprocal of the second fraction.